Sixteenth-Century Polymaths in the Print and Publishing Business in Basel: An Intersection of Interests and Strategies (1472–1513) - Sebastiani, Valentina (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
In sixteenth-century Europe the business of printing created small intellectual communities that had the ability to manage the exigencies of the market and those of culture. In this process of continual negotiation between the interests of publishers, authors, and readers, how did men of letters lend their erudition to the service of printing? How were they able to elicit the interest of printers in publishing their works? And, above all, to what extent did their collaboration with printers impact their careers? This brief investigation analyzes the work of polymaths such as Johann Heynlin, Conrad Leontorius, Konrad Pellikan, Sebastian Brant, Jacob Wimpfeling, and Johann Reuchlin—who, acting as translators, proofreaders, and literary and typographical experts, collaborated with the Basel printer Johann Amerbach—in order to shed light on the fruitful reciprocity of printing and erudition that shaped the careers of early modern scholars and erudites.